Start-up city : ten tales of exceptional entrepreneurship from Bangalore's software miracle /: ten tales of exceptional entrepreneurship from Bangalore's software miracle. (2014) - Bannerjee, Moloy K (Moloy Kumar); Bannerjee, Siddharth; Ranganath Sastry, P
No abstract available